2013
DOI: 10.21675/2357-707x.2013.v4.n2.518
|View full text |Cite
|
Sign up to set email alerts
|

Humanização da assistência de enfermagem em uma unidade de internação obstétrica

Abstract: Resumo: O estudo objetivou verificar o atendimento prestado pela equipe de enfermagem durante o trabalho de parto e parto. Optou-se pelo método quantitativo, descritivo, transversal e prospectivo. A coleta de dados foi realizada no período de maio a junho de 2011, abrangendo uma amostra de 30 puérperas de parto normal. Os resultados evidenciam que algumas atividades ainda estão em discordância com o que é recomendado pelo Programa de Humanização. É necessário o desenvolvimento de ações estratégicas, buscando a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
1
3
0
6
Order By: Relevance
“…In order to foster the good obstetric practices and ensure the right to safe care for both the mother and the baby, the promotion of woman and child health care networks is paramount to strengthen their autonomy and contribute to the reduction of risks. This assumption is consistent with the Stork Network, a policy recently launched by the Ministry of Health in order to reduce maternal mortality through initiatives aimed at ensuring the rights of women, from family planning to pregnancy, childbirth, and puerperium, with follow-up of the child from 0 to 24 months of age (18) .…”
Section: Discussionsupporting
confidence: 82%
“…In order to foster the good obstetric practices and ensure the right to safe care for both the mother and the baby, the promotion of woman and child health care networks is paramount to strengthen their autonomy and contribute to the reduction of risks. This assumption is consistent with the Stork Network, a policy recently launched by the Ministry of Health in order to reduce maternal mortality through initiatives aimed at ensuring the rights of women, from family planning to pregnancy, childbirth, and puerperium, with follow-up of the child from 0 to 24 months of age (18) .…”
Section: Discussionsupporting
confidence: 82%
“…17 Therefore, there is a need to qualify workers to develop skills to receive, attend, listen, dialogue, make decisions, support, guide and negotiate. Welcoming is a process in which workers and health services are involved and commit themselves to the responsibility of intervening in their field of action, considering their clientele and consequently their needs, seeking a warm, harmonious and humanized relationship to provide health at the individual and collective levels.…”
Section: Discussionmentioning
confidence: 99%
“…The professionals of several areas of health more than ever must participate actively in the care provided to the elderly. 27 One of the concerns in one of the studies conducted by medical students in the assessment of competences was regarding medication of the elderly regarding understanding your prescription, complete list of medications a patient, including those prescribed, herbs and prescription medicines, provide the dose for each drug, the frequency, the indication, the benefits and effects. 14 In a study conducted in Brazil showed that not all medications used were prescribed by doctors, some being used for own account.…”
Section: Discussionmentioning
confidence: 99%